SEBARAN MASYARAKAT MISKIN DAN PROGRAM BANTUAN LANGSUNG TUNAI (BLT) BAGI RUMAH TANGGA SASARAN DI KECAMATAN PANCORAN MAS KOTA DEPOK - JAWA BARAT - Habibullah Habibullah (Puslitbangkesos Kementerian Sosial RI, 2010)
Bantuan Langsung Tunai (BLT: Unconditional cash transfer) One of the poverty reduction program with controversial. Controversial because this program provides assistance in the form of cash which raised the com men sense that these programs make people lazy and this Program is carried out not on target. This study aims to map the distribution of the poor based on the BLT recipients database and processed using GIS software ArchView version 3.3. Besides, this study also identified the BLT program benefits to households in targeted (rumah tangga sasaran) in Kecamatan Pancoran Mas Kota Depok. This descriptive research with quantitative approach.Results showed Kelurahan Pancoran Mas is a slum area with indicator is a urban village with the most program recipients BLT program and with ven) poor category have the most in this urban village.When viewed from the benefit program for households, BLT program benefits to meet basic needs for poorest but the poor and near-poor categon) of the BLT program is a right as a citizen to obtain compensation for fuel price hike.Therefore, the pooerty reduction policy should refer to the categorization of poverty: poorest, poor and near poor. For the poorest caiegorq, the social assistance programs such as the BLT program is necessan) but for the poor and near-poor caiegoru of the most appropriate program is a program of communiiu empower-ment.